Using Learning Theories to Develop a Veterinary Student Preparedness Toolkit for Workplace Clinical Training - Routh, Jennifer; Paramasivam, Sharmini Julita; Cockcroft, Peter; Nadarajah, Vishna Devi; Jeevaratnam, Kamalan (Frontiers in Veterinary Science, 2022)
A theory is a set of interrelated propositions, concepts or definitions, which specifies the relationships between them, with the aim of explanation or making predictions(1). Learning theories are abstract descriptions which help us make sense of educational practice. Multiple theories can inform our understanding of a single concept, in this case: veterinary workplace clinical training (WCT), which occurs just prior to students’ graduation as competent veterinary surgeons. The competency movement has strongly influenced reforms in veterinary education and is considered important. In reflection of this, the term “preparedness” is operationalised here as a measure of the likelihood that the veterinary student is going to be a competent learner and participant during WCT. Preparedness itself is therefore important because it directly impacts performance. Workplace clinical training is explored through the lenses of cognitivist, social constructivist and socio-culturalist learning theories and used to inform student preparedness characteristics (“tools”) in terms of their behaviours, personal attributes, knowledge and skills, and awarenesses to optimise learning and participation. These form a new conceptual framework - the “Preparedness Toolkit”.